16.- BORGES’S POE: THE INFLUENCE AND REINVENTION OF EDGAR ALLAN POE IN SPANISH AMERICA - Rigal Aragón, Margarita (Nueva Revista del Pacífico, 2021)
In 1934, John Eugene Englekirk’s Edgar Allan Poe in Hispanic Literature was published. Englekirk’s work approached some Spanish authors who showed, according to him, the influence of Poe in their works; however, he focused mainly on South American writers. Since then, multiple researchers have worked on the relationship between Spanish speaking authors and this master of story telling. That is the case of the extensive bibliographical work prepared by Rafael Heliodoro Valle (1950) and by Hensley Woodbridge (1969). Several of them, before Emron Esplin, concentrated mainly on the bond between Borges and Poe. This was the case, for instance, of Maurice J. Bennet’s 1983 essay, “The Detective Fiction of Poe and Borges,” which presented one of the earliest comparative interpretations of Borges’s legendary story “La muerte y la brújula” [“Death and the Compass”] together with Poe’s Dupin trilogy. A decade later, in 1994, a milestone on the matter appeared: an interdisciplinary voyage through Poe’s and Borges’s analytic minds, John T. Irwin’s The Mystery to a Solution: Poe, Borges, and the Analytic Detective Story. Right before the turn of the century, Gabriella Tissera revisited, again, this link in Lois Davis Vines’s 1999 Poe Abroad.